KERAGAMAN DAN KELIMPAHAN MUSUH ALAMI HAMA PADA HABITAT PADI YANG DIMANIPULASI DENGAN TUMBUHAN BERBUNGA - , NIA KURNIAWATI, Dr. Ir. Nugroho Susetya Putra, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
A limited field investigation was done to observe the impact of flowering plants to the abundance and diversity of natural enemy of rice pest in a rice habitats. Two treatments, i.e. rice planting accompanied with flowering plants and without flowering plants were arranged on plots in the Faculty of Agriculture experimental station, University of Gadjah Mada, Banguntapan, Bantul, Yogyakarta. Each treatment was replicated three times. The results showed that flowering plants increase arthropods diversity including natural enemies significantly, help in improving yield and lower the incidence of rice pest, e.g. rice stemborer. Key word : flowering plant, natural enemy, diversity, abundance